Perbandingan Respons Dan Produksi Tanaman Karet (Hevea brasilliensis M.) Klon PB 260 Dan Rric 100 Terhadap Aplikasi Stimulan - Dewi Sartika Andriyani; Muhammad Tahir; Any Kusumastuti (AGRITROP, 2020)
This study aims to get a higher cup lump production in rubber plants that are given a stimulant treatment compared to rubber plants that are not given a stimulant. Higher levels of dry rubber in PB 260 that has been given a stimulant compared to the RRIC 100 who has been given a stimulant and clone that provide the best responses to the stimulant. This research was conducted at Afdeling 5 PTPN VII Padang Pelawi starting from March to May 2019. The method used a t-test with PB 260 and RRIC 100 clones. The observed variables were stem girth, tapping angle, tapping depth, tapping thickness, skin consumption, cup production lumps, and dry rubber content. The results obtained by the use of stimulants increased cup lump production in two clones studied, RRIC 100 clones gave the best response to stimulants compared with PB 260 clones.